The minimal Hilbert basis of the Hammond order cone - Abul Naga, Ramses H (Springer, 2022)
We characterize the minimal Hilbert basis of the Hammond order cone, and present several novel applications of the resulting basis. From the basis, we extract an invertible matrix, that provides a numerical representation of the Hammond order relation. The basis also enables the construction of a space—that we call the Hammond order lattice—where order-extensions of the Hammond order (i.e. more complete relations) may be derived. Finally, we introduce a class of maximal linearly independent Hilbert bases, in which the specific results derived in relation to the Hammond order cone, are shown to hold more generally.
Keywords: Hilbert, Algebras de; Measurement of social welfare; Order relations induced by convex cones; Hammond order; Hilbert bases